HUBUNGAN KEBIASAAN SARAPAN, KECUKUPAN ZAT GIZI DAN CAIRAN DENGAN DAYA KONSENTRASI ANAK SEKOLAH DASAR - Wida Ratna Yunita; Triska Susila Nindya (Universitas Airlangga, 2017)
Breakfast habits, nutritional and fl uid adequacy is very important for students learning concentration. The purpose of this research was to analyze the relationship between breakfast habits, nutritional and fl uid adequacy with thelearning concentration in students. This was an observational research with cross sectional design, conducted in SDN Sukomanunggal IV Surabaya with 60 respondents. Characteristics of respondents, breakfast habit, food intake, fl uidintake and learning concentration test were collected. The breakfast habit was measured by questionnaire. The nutrition and fluid intake were measured using recall 3×24 hours and the concentration was measured by using bender gestalttest. The data was analyzed by chi square test and logistic regression. Respondents have an adequate of carbohydrate (63.3%), protein (60.0%), fat (61.7%) and vitamin C (58.3%). Meanwhile inadequate of energy (51.7%), iron (53.3%) and fluid (56.7%). There are signifi cant correlation between breakfast habit, energy, carbohydrate, protein, Fe, vitamin C and fl uid adequacy level with learning concentration. There was no signifi cant correlation between fat adequacy level with learning concentration. Therefore parents need to provide the breakfast regularly.